2022
DOI: 10.1371/journal.pone.0271680
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practice and its associated factors among diabetic patients attending public hospitals in Gurage zone southwest, Ethiopia

Abstract: Background Diabetes is a chronic disease that requires lifelong medical treatment and lifestyle modifications. Even though patients often neglect their own needs, self-care is an important factor in preventing and delaying complications related to diabetes. There are limited studies about self-care practice, and most of the studies conducted in Ethiopia focused on some parts of the recommended self-care practice. Therefore, this study aimed to assess the self-care practice and associated factors among diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
2
1
Order By: Relevance
“…This too is consistent with many other studies in the literature [ 33 35 ]. Though, Kong et al [ 22 ] reported SCB at a high level among type 2 diabetes patients, and Abate et al [ 36 ] and Emire et al [ 25 ] reported them at a low level, all of which are in contrast to our findings. The differences may be due to different study populations, varying levels of awareness and patients’ attitudes toward self-care and/or the use of different tools.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This too is consistent with many other studies in the literature [ 33 35 ]. Though, Kong et al [ 22 ] reported SCB at a high level among type 2 diabetes patients, and Abate et al [ 36 ] and Emire et al [ 25 ] reported them at a low level, all of which are in contrast to our findings. The differences may be due to different study populations, varying levels of awareness and patients’ attitudes toward self-care and/or the use of different tools.…”
Section: Discussioncontrasting
confidence: 99%
“…The literature on self-care behaviors (SCB) and self-efficacy in patients with type 2 diabetes shows inconsistent findings. Some studies have found a high level of SCB and a strong correlation between self-efficacy and self-care [ 22 24 ], while others have reported a low or moderate level of SCB and a weak or non-significant correlation between self-efficacy and self-care [ 25 27 ]. Moreover, the rates of SCB, self-efficacy and health deviation self-care requisites (HDSCR) vary across different studies [ 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, 337 study participants (42.4%) had good adherence to self-care practice. The finding is in line with the studies conducted in western Ethiopia in 2020 (42.7%) 14 and in the Gurage Zone in 2022 (39.6%), 45 and it is higher than the study conducted in Tigray in 2017 (37.3%). 39 The possible variation of this result might be related to the period gap resulting in some improvements in the health care systems, 46 socio-demographic characteristics, and methods in which the current study used multi-facility and a large sample size, while the previous study used a single institution and a lower sample size (278 patients).…”
Section: Discussionsupporting
confidence: 90%
“…This finding was consistent with the study conducted in Ethiopia where females were 2.4 times more likely to have poor self-care practice than males (AOR; 2.40, 95% CI 1.31-4.40). 19 This could be due to lower status of women in society and neglect of their health care needs. Optimum glycaemic control is needed to prevent micro-vascular complications.…”
Section: Discussionmentioning
confidence: 99%